Psychophysical effects of music in sport and exercise: an update on theory, research and application - Terry, P. C.; Karageorghis, C. I. (2006 Joint Conference of the Australian Psychological Society and the New Zealand Psychological Society, 26-30 Sept 2006, Auckland, New Zealand., 2006)
This paper provides a narrative review of recent theory, research and applications pertaining to the psychophysical effects of music in the sport and exercise domains. A conceptual framework is presented, which emphasises that the principal benefits of music - improved mood, arousal control, reduced perceived exertion, enhanced work output, improved skill acquisition, flow states, dissociation from feelings of pain and fatigue - are determined by the four factors of rhythm response, musicality, cultural impact, and extra-musical associations. A simple example involves the tendency for humans to respond to the rhythmical qualities of music by synchronising movement patterns to tempo. Synchronous music has been reliably shown to produce an ergogenic effect. Therefore, if athletes or exercisers work in time to music, they will likely work harder for longer. Responses to asynchronous, or background, music are less predictable and beneficial effects are less reliable, although considerable potential remains if certain principles are followed. An example is that fast, upbeat music produces a stimulative effect whereas slow, soft music produces a sedative effect. Several evidence-based examples are presented of how music has been used effectively in our work as applied practitioners with groups ranging from exercise participants to elite athletes.